CAMPUR KODE UNGKAPAN CINTA DALAM LIRIK LAGU BERBAHASA JEPANG - Putra, Devi Andrisko; Hermandra, Hermandra; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: This research purpose to know about code mixing love expression on japanese song lyric. In addition the purpose of this research is to describe form about kind code mixing love expression on japanese song lyric. Method are use in this research is listening method or observation method. Object of this research is populer song in 2010 until 2012 that the theme is about love. Technical of material collection is reading method, book research method, and writing method. Research result show that in 5 japanese song are an object of the research there is 2 kind form is 5 code mixing love expression concrate phrase and 11 code mixing love expression concrate clause. And from analysis result 5 song that got 27 materials contains language kind which divided in 6 kind language kind that one time mutual manner appear, five time casual manner appear, ten time familiar manner, four time scientific manner, six time colloquial manner appear, and one time bawdy manner appear.Key Words: Mixing code, Language Kind, Songs.